Frequency and obstetric complication of uterine leiomyoma in pregnancy - Mehmoodah, Mehmoodah; khatoon, Saima; Rani, Bela; Parveen, Tooba; Khushboo, Khushboo; Hanif, Maria (Journal of Neonatal Surgery, 2025)
Objectives:  To determine the frequency of leiomyoma in pregnant females presenting for antenatal checkup.  To determine the outcome of pregnancy complicated with leiomyoma. Study design Descriptive Study.: Setting This study was conducted at the Department of Obstetrics & Gynaecology, SMBBMU, Larkana, Pakistan. Duration Six months after the approval of the synopsis from January 31, 2023 to July 30, 2023. Materials and methods All patients who fulfilled the inclusion criteria and visited SMBBMU, Larkana were included in the study. Informed consent was taken after explaining the procedure, risks and benefits of the study. In our study, All the collected data were entered into the proforma attached at the end and used electronically for research purposes. Results: The mean ± SD of age was 29.9±6.3 years. Leiomyoma was found in 49 (30.6%) women. In the distribution of complications spontaneous abortion was found in 6 (12.2%), intrauterine growth restriction in 17 (34.7%), the premature rupture of membranes was noted in 11 (22.5%) women, cesarean section in 29 (59.2%), vaginal delivery 20 (40.8%), preterm delivery 14 (28.6%) while stillbirth was noted in 5 (10.2%). Conclusion: It is to be concluded that leiomyoma was commonly prevalent in pregnant females while cesarean section was noted as the most common leiomyoma complication followed by intrauterine growth restriction and premature rupture of membranes. More well-controlled prospective trials are needed to validate the current findings